Synthesis and characterization of (1 − x)(La0.6Ca0.4MnO3)/x(Sb2O3) ceramic composites. (2nd January 2019) - Amri, N.; Nasri, M.; Triki, M.; Dhahri, E.
ABSTRACT: The composites ((1 − x )(La0.6 Ca0.4 MnO3 )/ x (Sb2 O3 )) ( x = 0.00, 0.07 and 0.12) were synthesized by conventional solid-state reaction method. The results of X-ray diffraction (XRD) and SEM indicate that Sb2 O3 and LCMO coexist in the composites and Sb2 O3 mainly segregates at the grain boundaries of LCMO. Furthermore, the magnetic study shows a typical variation. The resistivity of the composite samples was measured at the applied magnetic fields of 0T, 2T and 5T. All the specimens undergo a metallic–semiconductor transition at the temperature Tρ . The temperature dependence of resistivity shows that the transport behavior of the composites is governed by the grain boundaries. It is suggested that the Sb2 O3 addition, acts as a separation layer between grains. The ρ- T fit well with the phenomenological equation for conductivity under a percolation approach. Magnetoresistance (MR) has been found to reach a maximum value with Sb2 O3 addition. The magnetocaloric properties of LCMO based on resistivity measurements were investigated. We measure the magnetic entropy change ΔSM from the resistivity which is similar to that calculated from the magnetic measurements. Finally, the TCR curves show good value under zero magnetic field, which makes it a good candidate for bolometer applications.